EXPERIENCE REPORT FROM ONLINE AND HYBRID TEACHING OF A PROJECT-ORIENTED DATABASES COURSE USING AN ADAPTIVE ITERATIVE PROCESS OF FORMATIVE AND SUMMATIVE ASSESSMENT - Ajanovski, Vangel (IATED, 2023)
As a proponent of the learning by doing approach, the author organizes the Databases course for Computer-Science and Software Engineering students in a project-oriented manner. The students are divided in small teams of 2-3 persons, working on separate database projects. Each team is free to self-organize and decide on the topic of their project - usually it is the development of a database design and a web or desktop application that uses the designed database. The projects are developed in several phases. Mandatory phases consist of: team and project inception, entity-relationship design, transformation to a relational schema, use-case design and database implementation with SQL queries, early prototype application development. Optional phases include: database reorganization and normalization and full-stack application development. The projects are assessed as teams, phase by phase. On the other hand the course also includes personalized assessment of each student's knowledge, via a practical test and a theoretical test. The practical test, assesses student ability to use SQL in a real database, while the theoretical tests assesses student knowledge across the typical topics of the databases course material in a theoretical and applied manner. In the past, all groups worked on a fixed schedule, where each project phase lasted for 2-3 weeks and the project ended with the semester and tests were organized in three fixed exam sessions. Since the COVID-19 epidemic, the course turned entirely online or hybrid (depending on the current health situation), and the fix schedule had to be abandoned, to accommodate the public health crisis and the situation of each student, in favor of a completely adaptive and iterative schedule of project work and assessment. The course material is divided in several groups of topics, and each student can pass the respective course materials in their own pace and in a coordinated way to how they pass through each project phase as a group. Tests are organized as often as needed (a sufficiently large group of interested students has asked for a test) and each student is tested on parts of the material they are ready for, and when they are ready for it. This is only possible since two systems were introduced in the course - a project-organization and resource provisioning system and a testing database and semi-automated assessment system. The testing system is in production since 2019 and the resource provisioning system since 2021. Internal self-evaluation indicates quite positive experience and satisfaction by the students from the organization of the course, the intensity of communication with the teacher, the project component, what they have learned and even stronger satisfaction with the use of the special practice and testing system. This paper describes in detail the course organization and system use, and reports on the experience and evaluation of the use. Both introduced systems are published as open-sourced and members of the community are invited for future collaboration.
Keywords: Databases, SQL testing, automated sql assessment, practice for test systems, testing systems, project organization, project resource provisioning